Implementation of the Maternal and Neonatal Tetanus Elimination (MNTE) Program at the Banjarmasin Health Center - Suhartati, Susanti; Handayani, Lisda (DINAMIKA KESEHATAN: JURNAL KEBIDANAN DAN KEPERAWATAN, 2021)
Background In an effort to reduce the incidence of neonatal tetanus, Indonesia has carried out various strategies, namely by implementing safe and clean assistance, high and even coverage of TT techniques, and administering neonatal tetanus surveillance. One of the scopes of routine TT training is the implementation of the Maternal and Neonatal Tetanus Elimination (MNTE) program. The Maternal and Neonatal Tetanus Elimination Program (MNTE) is implemented by all Puskesmas as the first service for the use of Tetanus Toxoid. Objective Describe the causes of low TT coverage at the Banjarmasin City Health Center and describe the obstacles faced in the process of implementing the Maternal and Neonatal Tetanus Elimination (MNTE) program in Banjarmasin. Method This research is a quantitative descriptive study using Cross Sectional. With Acidental Sampling with a total of 150 respondents consisting of pregnant women and 25 midwives at the Banjarmasin Health Center. Results From 150 pregnant women respondents, there are still 28 people or 18.7% of pregnant women who have never been able to use TT, there are only 6 pregnant women or 4% of pregnant women with TT 4 status and there are 54 pregnant women or 36% of women. pregnant with TT 1 status. A total of 78 people or 52% have less knowledge of TT techniques. As many as 88 people or 58.6% have a negative attitude towards TT, as much as 59.4% of pregnant women stated that the role of officers is still lacking in explaining the TT technique. Service documentation is only centered on service providers, documentation is not clearly accessible or readable by service recipients. low parity need more effort in utilizing TT. Lack of information and knowledge causes there are still pregnant women with negative attitudes towards exercise. Conclusion MNTE services at the Banjarmasin Health Center require increased promotion efforts, and media documentation that can be owned by women of childbearing age to find out TT and can fulfill TT status up to TT 5. Keywords Immunization TT, Tetanus, MNTE